The Subprime Crisis and the Asian Crisis - Remarks from a Comparative Analysis - Jurek, Michał; Marszałek, Paweł (Kryzys o zwiększonym ryzyku i kryzys azjatycki - uwagi wynikające z analizy porównawczej, 2010)
The paper reveals whether the existing premises of currency and banking crises can be implemented while searching for the roots of the contemporary global financial crisis. To answer this question, we attempt to find out whether the current crisis is similar to the one that exploded in the countries of Southern and Western Asia in the nineties. We find that, apart from the constant increase in the volume of capital flows around the world, the development of techniques of the financial instruments' creation as well as institutional forms of financial institutions, the main reasons for the crises' outburst remain unchanged. Among them one can distinguish weakening economic fundamentals and structural imperfections, reflected in the lack of transparency of financial instruments and financial markets.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 125, s. 37-63
Keywords: subprime crisis; Asian crisis; financial markets